Annual review of competence: trainees' perspective. (December 2013) - Goodyear, Helen; Wall, David; Bindal, Taruna
Summary Background: An annual review of competence progression (ARCP) is compulsory for all UK specialty trainees. Aim: We explore specialty trainees' views on ARCPs, including the usefulness of annual review, and how well prepared they felt for it. Methods: A 15‐item questionnaire was completed anonymously by 63 paediatric specialty trainees following their ARCPs in the West Midlands Deanery. After further trainee and trainer education on ARCPs, 21 trainees participated in telephone semi‐structured interviews. Results: Seventy‐six per cent of paediatric specialty trainees found having an ARCP helpful, although 70 per cent did not feel well informed about the process: this did not vary by training year or gender. Apart from trainees valuing a regional review of progress, the other key themes from the semi‐structured interviews were negative around ePortfolio, IT, lack of consultant training and willingness to undertake assessments, being unaware of the evidence needed for ARCP and electronic ARCP feedback. Conclusion: Although three‐quarters of paediatric trainees found having an ARCP helpful, they did not feel prepared for the ARCP. Educating both trainees and trainers about ARCPs and the required portfolio evidence is continuing; however, we believe trainees will only truly feel prepared for their ARCPs after successfully addressing the more challenging issues of good IT infrastructure in each trust, with consultants readily undertaking workplace‐based assessments (WBAs) and with educational supervision being of a consistently high standard.